Pattern of Breast Cancer in Women at Child-bearing Age, its Risk Factors and Clinicopathological Evaluation in Tertiary Level Hospital (Journal of Rangpur Medical College, 2024)
Background: Carcinoma breast is the leading cancer in female in Bangladesh, increasing significantly due to urbanization and adoption of western life style. Objective: This study aimed to systematically understand the pattern of breast cancer, its risk factors and clinicopathological evaluation in women at their childbearing age. Methods: A cross sectional observational study, data was collected from 50 patients of histopathologically confirmed breast cancer in the department of Surgery, Combined Military Hospital, Dhaka from 2022 to 2023. Results: The majority of the cases were 41-45(42%) years age with mean presentation was 43.55 (SD-/+9.63) years. Invasive ductal carcinoma was the most common subtype 86%, followed by ductal carcinoma in situ (8%). Of the cases 2% were nullipara and 46% had two children. Median age of at 1st birth was 21 years. A significant proportion (16%) had family history of breast cancer. 98% patients gave history of breast feeding. Conclusions: Breast cancer is increasingly occurring in younger age groups in Bangladesh, results suggested a mixture of different factors in women like age of menarche, age of first child birth, parity, history of breast feeding and family history poses higher risk for breast cancer.J Rang Med Col. March 2024; Vol. 9, No. 1:16-21